2004
DOI: 10.1128/mcb.24.14.6184-6193.2004
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Capping Enzyme Activity Is Coupled to an Early Transcription Elongation

Abstract: One of the temperature-sensitive alleles of CEG1, a guanylyltransferase subunit of the Saccharomyces cerevisiae capping enzyme, showed 6-azauracil (6AU) sensitivity at the permissive growth temperature, which is a phenotype that is correlated with a transcription elongation defect. This temperature-sensitive allele, ceg1-63, has an impaired ability to induce PUR5 in response to 6AU treatment and diminished enzyme-GMP formation activity. However, this cellular and molecular defect is not primarily due to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…It was observed earlier that an excess amount of the methylation donor SAM inhibited transcription initiation [64] and that the 5′ capping enzymes were able to repress transcription [65], suggesting that the 5′ capping reaction and the subsequent release of the capping enzymes are both critical for the transition from transcriptional initiation to elongation. Indeed, further studies revealed that both Ser5 phosphorylated CTD and the transcription elongation factor Spt5 help recruit the 5′ capping enzymes, which then counteract the inhibitory NELF complex, thereby facilitating promoter clearance and enhancing the entrance of the initially paused RNAPII to the mode of productive transcription elongation [66][67][68]. After this transition, the CTD phosphatase FCP1 seems responsible for removing Ser5 phosphates and dismantling the capping enzymes [20,68].…”
Section: Transcription/rna Processing Coupling: a Mutually Beneficialmentioning
confidence: 99%
“…It was observed earlier that an excess amount of the methylation donor SAM inhibited transcription initiation [64] and that the 5′ capping enzymes were able to repress transcription [65], suggesting that the 5′ capping reaction and the subsequent release of the capping enzymes are both critical for the transition from transcriptional initiation to elongation. Indeed, further studies revealed that both Ser5 phosphorylated CTD and the transcription elongation factor Spt5 help recruit the 5′ capping enzymes, which then counteract the inhibitory NELF complex, thereby facilitating promoter clearance and enhancing the entrance of the initially paused RNAPII to the mode of productive transcription elongation [66][67][68]. After this transition, the CTD phosphatase FCP1 seems responsible for removing Ser5 phosphates and dismantling the capping enzymes [20,68].…”
Section: Transcription/rna Processing Coupling: a Mutually Beneficialmentioning
confidence: 99%
“…For instance, stimulation of CE by HIV Tat promotes read-through of the viral genome (20,21). CE has been implicated in the formation of an early elongation checkpoint, as has been observed in 5Ј-paused Pol II complexes (15,(22)(23)(24)(25). Cotranscriptional capping is effectuated by the specific interaction between a CE and its cognate RNA polymerase that supports a stoichiometric CE-polymerase complex (13,26), as exemplified in certain viral transcription/processing systems in each of which the transcription of viral genes is mediated by a single virus-encoded RNA polymerase (27).…”
mentioning
confidence: 99%
“…Thus, CE-dependent RLF in yeast would only occur, if at all, at an early phase of transcription. Indeed, a ceg1 mutant strain with diminished GTase activity showed reduced Pol II elongation at promoterproximal regions (18). It is conceivable that this process in some way involves RLF.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown that CE can act as a transcriptional regulator. In vitro experiments in yeast demonstrated that Cet1 represses transcription reinitiation (17), whereas mutation of ceg1 and abd1 affects transcription elongation (18,19). Finally, human CE is capable of relieving transcription repression by the negative elongation factor (NELF) (20).…”
mentioning
confidence: 99%